2017
DOI: 10.1371/journal.pone.0172934
|View full text |Cite
|
Sign up to set email alerts
|

Innovative exercise device for the abdominal trunk muscles: An early validation study

Abstract: BackgroundExercise is one of the few treatments that provide significant improvements in chronic low back pain (CLBP). We developed an innovative exercise device for abdominal trunk muscles. This device can be used in a sitting or standing position and contains a built-in system to measure abdominal trunk muscle strength. We examined whether subjects can adequately use the device to perform the exercises and measure their abdominal trunk muscle strength.MethodsWe collected data on the body height, body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Previous studies reported that muscle strength measurement and device-driven strengthening exercises did not exert adverse effects in young adults [ 17 , 18 ]. Similarly, in the present study, use of the device for 12 weeks did not produce adverse effects in elderly patients with CLBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that muscle strength measurement and device-driven strengthening exercises did not exert adverse effects in young adults [ 17 , 18 ]. Similarly, in the present study, use of the device for 12 weeks did not produce adverse effects in elderly patients with CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…The device resembles a sphygmomanometer, with an inflatable cuff and a mechanical manometer for measuring pressure [ 17 ] ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described in detail [18], the device has an inflatable cuff and a built-in mechanical manometer to measure pressure. To take a measurement, the cuff placed around the subject’s abdomen is inflated, and an adequate pressure (i.e., the baseline pressure: Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We developed an innovative exercise device for the abdominal trunk muscles (Fig. 1: trunk muscle exercise device; Nippon Sigmax Co., Ltd., Shinjuku-ku, Tokyo, Japan) [18]. Using this device, subjects can perform strengthening exercises for the abdominal trunk muscles in a sitting position without the need for trunk movement, including movement of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%